Prostaglandin E2 and Receptors: Insight Into Tumorigenesis, Tumor Progression, and Treatment of Hepatocellular Carcinoma - Chen, Chao; Guan, Jun; Gu, Xinyu; Chu, Qingfei; Zhu, Haihong (Frontiers in Cell and Developmental Biology, 2022)
Hepatocellular carcinoma (HCC) is a common primary liver cancer with 750,000 annual incidence rates world widely. PGE2, usually known as a pro-inflammatory cytokine, is over-expressed in various human malignancies including HCC. PGE2 bind to EP receptors in HCC cell to influence tumorigenesis or enhance tumor progression through multiple pathways such as EP1-PKC-MAPK, EP2-PKA-GSK3β and EP4-PKA-CREB pathway. In the progression of hepatocellular carcinoma, PGE2 can promote the proliferation and migration of liver cancer cells by affecting hepatocytes directedly and the tumor microenvironment (TME) through ERK/COX-2/PGE2 signal pathway in hepatic stellate cells (HSC). In the treatment of hepatocellular carcinoma, there is drugs as T7 peptide and EP1 antagonist ONO-8711 targeting Cox-2/PGE2 axis to inhibit progression of tumor. In conclusion, PGE2 show a traditional target with pleiotropic effects in tumorigenesis and progression of HCC to develop a new potential clinical impact. For the treatment study focusing on the COX-PGE2 axis, the exclusive usage of NSAIDS or COX-2-inhibitors may be replaced by combination of selective EP antagonists and traditional anti-tumoral drugs to alleviate severe side effects and approach better outcomes.